Responders and nonresponders to pharmacotherapy and allergen immunotherapy - Marek Jakalski; Andrzej Bozek; G. Walter Canonica (Taylor & Francis Group, 2019)
Allergen immunotherapy (AIT) is a very useful therapy for allergic rhinitis. However, some patients do not achieve the expected results. The aim of the study was to investigate the potential factors that could affect the result, either good or poor, from AIT. Methods: A retrospective analysis of 1624 patients with allergic rhinitis who underwent AIT and 1519 matched patients who underwent only symptomatic therapy (without AIT) was performed. Symptoms, medications scores and quality of life related to allergic diseases before and after therapy were recorded. Cluster analysis on all of the patients was performed to find any associations between responsiveness to therapy and the analyzed parameters. Responsiveness to therapy was assessed by the Mailing criteria. Results: A total of 1266 (77.8%) patients from the AIT group met the criterion of 30% or greater improvement, and 1061 (65.2%) of these patients met the threshold of 60% or greater improvement according to the Mailing criteria. Patients who had a frequently better response to AIT were highly represented in the two clusters. There were subjects with a short history of allergic rhinitis and concomitant allergy to grass pollen or house dust mites. Patients with a prolonged duration of allergic rhinitis before therapy and with polysensitization were more frequently worse responders to AIT. Conclusion: Responsiveness to therapy, including that to AIT, is difficult to assess. However, there were associations suggesting that short-term allergic rhinitis and monovalent allergies to grass pollen or mites could correspond to a better response to AIT.